Fibre laser piercing of mild steel: the effects of power intensity, gas type and pressure - Hashemzadeh, M.; Powell, J.; Voisey, K.T. (Elsevier, 2014)
Laser piercing is used to generate a starting point for laser cutting. The pierced hole is normally larger than the kerf width, which means that it cannot lie on the cut line. An experimental program investigating the piercing process as a function of laser and assist gas parameters is presented. An Nd:YAG fibre laser with a maximum power of 2 kW was used in continuous wave mode to pierce holes in 2 mm thick mild steel. Oxygen and nitrogen were used as assist gases, with pressures ranging from 0.3 to 12 bar. The sizes, geometries and piercing time of the holes produced have been analysed. The pierced hole size decreases with increasing gas pressure and increasing laser power. Oxygen assist gas produced larger diameter holes than nitrogen. A new technique is presented which produces pierced holes no larger than the kerf with and would allow the pierced hole to lie on the cut line of the finished product – allowing better material usage. This uses an inclined jet of nitrogen when piercing prior to oxygen assisted cutting.